Physicochemical properties and fatty acids composition of sudanese moringa oleifera seed oil - Abeer A., Idris; Azhari, Nour Hamid; Omer Ishag, Omer A.; Mahmoud, Ali; Erwa, Ibrahim Y.; Abdurahman, Nour Hamid (Turkish Chemical Society, 2020)
Moringa oleifera is a robust and fast growing tree considered as one of the most beneficial trees worldwide since almost all parts of it used as food, medicines and for industrial purposes. The aim of this study was to investigate the physicochemical properties and fatty acid composition of M. oleifera seed oil. The oil was extracted by Soxhlet using n-hexane; the physicochemical properties of the seed oil were assessed by standard and established methods, as well the fatty acid composition of the seed oil was determined by GC-MS. The golden yellow with characteristic odor oil obtained from the seeds had the following physicochemical properties: yield, 42.87%; freezing point, 0 °C; melting point, 21 °C; boiling point, 225 °C; refractive index (25 °C), 1.447; iodine value, 96.6 g/100g of oil; peroxide value, 7.6 meq.O2/kg of oil; free fatty acids, 0.07%; acid value, 1.4 mg of KOH/g of oil; saponification value, 185.2 mg KOH/g of oil; unsaponifiable matter, 3.2; moisture and volatile value, 4.91 (wt.%); density, 0.900 g/cm3; viscosity, 60.99 mm2/s; specific gravity, 0.907. The fatty acids composition showed that oleic- acid (51.74%) was the major fatty acid and followed by behenic- (10.54%), palmitic- (9.20%), stearic- (8.46%), arachidic- (6.41%), gondic- (4.88%), lignoceric- (3.08%) and palmitoleic acid (2.85%). Therefore, more and advanced research should be undertaken for this abundant source of natural oil for edible oil and possible industrial applications.